Contamination Features and Source Apportionment of Heavy Metals in the River Sediments around a Lead-Zinc Mine: A Case Study in Danzhai, Guizhou, China - Rongguo Sun; Yue Gao; Jing Xu; Yang Yang; Yutao Zhang (Journal of Chemistry)
The spatial patterns, ecological risks, and sources of heavy metals (HMs), including Pb, Zn, Mn, Cu, Cd, Hg, and As in river sediments, were identified around a lead-zinc mine of Danzhai, Guizhou, China. The concentrations of selected HMs and their coefficient variations indicated that the river sediments around this typical lead-zinc mine were obviously contaminated with HMs. Anthropogenic activities had further enhanced the accumulation of HMs. The higher contents of the most common selected HMs were mainly distributed in the area close to the lead-zinc mine. Based on the combined evaluations of the single factor pollution index, geo-accumulation index, and potential ecological risk index, it indicated that the ecological risks of Hg, Cd, Zn, and Pb were high or extremely high, and of Mn, Cu, and As were slight or none in the sediments around this lead-zinc mine. It was found that lead-zinc mining and smelting activities, coal mining activities, and agricultural activities (livestock and poultry breeding) are the primary sources of selected HMs, based on the results of correlation analysis together with principal component analysis (PCA) and positive matrix factorization (PMF) model. The pollution of HMs in the river sediments around a lead-zinc mine was predominantly caused by lead-zinc mining and smelting activities. Therefore, for environmental persistence, lead-zinc mining and smelting activities should be given careful consideration and under close surveillance.